ANALISIS FAKTOR PENGIRIMAN REMITAN OLEH PEKERJA MIGRAN SUKU BATAK DI KOTA DENPASAR KE DAERAH ASAL PADA MASA PANDEMI COVID 19 - Purba, Ayia Br; Sudibia, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.03.TAHUN.2022, 2022)
This study aims to analyze the effect of income, expenditure, and number of family members in the area of ??origin on remittances sent by Batak migrant workers in Denpasar to their hometown and to analyze the strategies of Batak migrant workers residing in Denpasar City to survive during the COVID-19 pandemic. The sampling technique in this study was quota sampling with 100 respondents, then processed and analyzed with multiple linear regression analysis. The results showed that income, consumption expenditure, and number of family members simultaneously and significantly affected the number of remittances sent; Income has a positive and significant effect on the amount of remittances, meanwhile, consumption expenditure and the number of family members have no effect on the amount of remittances sent; income is a factor that has a dominant influence on the amount of remittances, and; the COVID-19 pandemic affects income so that migrant workers survive by reducing consumption expenditure and the amount of remittances to their hometown.